Formação de professores e ensino híbrido : perspectivas e desafios na educação superior - Lopes, Julita Batista da Cruz (2020)
This research has as general objective to analyze the potentialities and the limits of the blended learning in the initial formation of the graduates of the courses of Letters, Pedagogy and Chemistry, with a view to the identification of interactive learning interfaces. It is assumed that undergraduate courses can develop knowledge and skills, attitudes and values in future teachers, who teach them to (re) build their own knowledge and practices within the culture of hybridism and multimodality before an education as a social practice, which forms subject from teaching and learning from a perspective of coexistence. In addition, this study is justified by the fact that contemporary society lives immersed in a scenario of digital and networked technologies, being relevant to the area of education to follow the advances within a sociocultural configuration in which we live. Initial training is at the center of debates about teacher professionalization and enhancement. This is a qualitative investigation, regarding the nature of the data, from the application of a questionnaire to 44 undergraduate students during classes in the disciplines of Information and Communication Technology in Education; Pedagogical Practices - Digital Technologies and Innovations for Teaching, in the second semester of 2019. The results enabled an analysis of the use of technologies in the context of the hybrid approach, with a view to promoting changes in basic and higher education in the face of different methodologies that allows the redefinition of collaborative learning. It was also noticed the need for training based on reflection-action-reflection, which supports the (re) construction of (self) formative trajectories in the hybrid and multimodal spaces of educational institutions.